A hydrogen production system based on quantum dot light-driven pet plastic degradation coupling water reduction
By using quantum dot-based light-driven degradation of PET plastic coupled with water reduction to produce hydrogen, the problems of low photocatalyst activity and high cost were solved, achieving efficient hydrogen generation and degradation of PET plastic, thus improving the system's economic efficiency and catalyst stability.
Patent Information
- Application Number
- CN202310758186.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-25
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-06-25
AI Technical Summary
Existing light-driven water reduction hydrogen production technologies suffer from low photocatalyst activity, require stirring to maintain a suspension for light energy absorption, are costly, and necessitate the addition of sacrificial agents, limiting their large-scale application. Furthermore, there is a large volume of PET plastic waste with no effective treatment methods.
A quantum dot-rich, edge-defect-rich quantum dot-driven PET plastic degradation coupled with water reduction hydrogen production system is employed. Water-soluble, edge-defect-rich quantum dots are used as catalysts, combined with PET plastic as an oxidative degradation sacrificial agent. This avoids the stirring process and utilizes sunlight to simultaneously degrade the plastic and generate hydrogen.
It achieves efficient hydrogen generation and degradation of PET plastic under stirring-free conditions, improving the system's economic efficiency and catalyst activity. The generation rate reaches 2.1 mmol/g/hour, solving the problems of low photocatalyst activity and high cost, while also enabling the recycling of plastic.
Smart Images

Figure CN116803894B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of light-driven water reduction hydrogen production technology, specifically to a quantum dot-based light-driven PET plastic degradation coupled with water reduction hydrogen production system. Background Technology
[0002] Photo-driven reduction of water to produce sustainable hydrogen is a novel technology that directly utilizes light energy, using water as a raw material, to reduce it into high-calorific-value fuel hydrogen through semiconductor materials. Electrons within the semiconductor material are exposed to sunlight, causing their valence band electrons to transition to the conduction band. These conduction band electrons react with water to form hydrogen, while the holes left in the valence band undergo oxidation. This system typically consists of a catalytically active semiconductor photocatalyst, a reaction solvent, a sacrificial agent for coupling holes, and external reaction devices. Its structure is simple, and compared to technologies that first generate hydrogen through photovoltaic power generation and then electrolyze water in an electrolyzer to produce hydrogen, it has lower device costs. Currently, the large-scale practical application of light-driven reduced water hydrogen production technology is mainly limited by the following aspects: First, the activity of the photocatalyst is relatively low, usually requiring the loading of precious metals (such as platinum, gold, etc.); Second, at present, a large number of photocatalysts in this technology need to be continuously stirred to maintain the suspension form in actual operation to absorb light energy, which hinders the development of this technology from the perspective of energy saving; Third, limited by the band gap position of semiconductor photocatalysts, the system usually introduces sacrificial agents (such as ascorbic acid, isopropanol, etc.) to consume holes in the valence band, thereby promoting carrier separation and increasing the hydrogen production rate. However, these hole sacrificial agents also require additional costs, reducing the economics of the system.
[0003] Meanwhile, the amount of plastic waste has been enormous in recent years. Due to its advantages such as good water resistance and durability, global plastic production has remained high. Among them, polyethylene terephthalate (PET) plastic is a common plastic with huge production and usage. Its monomer is obtained by esterification reaction of terephthalic acid and ethylene glycol, resulting in a huge amount of waste. At present, there is an urgent need for suitable treatment methods. Summary of the Invention
[0004] To address the aforementioned technical problems, the present invention aims to provide a quantum dot-based light-driven PET plastic degradation coupled with water reduction hydrogen production system, thereby solving the problems of low activity, need for stirring, and high cost of existing photocatalysts.
[0005] The technical solution of the present invention to solve the above-mentioned technical problems is as follows: a quantum dot light-driven PET plastic degradation coupled with water reduction hydrogen production system is provided. The system includes a stoppered glass bottle, which contains water-soluble quantum dots rich in edge defects, deionized water and polyethylene terephthalate fragments.
[0006] Based on the above technical solution, the present invention can be further improved as follows:
[0007] Furthermore, when the volume of the stoppered glass bottle is 45-55mL, the mass ratio of the water-soluble quantum dots rich in edge defects, deionized water, and polyethylene terephthalate fragments contained therein is 0.18-0.21mg: 4-6mL: 90-110mg.
[0008] Furthermore, when the volume of the stoppered glass bottle is 50 mL, the mass ratio of the water-soluble quantum dots rich in edge defects, deionized water, and polyethylene terephthalate fragments contained therein is 0.2 mg: 5 mL: 100 mg.
[0009] Furthermore, the diameter of the polyethylene terephthalate fragments is 0.4-0.6 cm.
[0010] Furthermore, the diameter of the polyethylene terephthalate fragments is 0.5 cm.
[0011] Furthermore, water-soluble quantum dots rich in edge defects were prepared by the following method:
[0012] (1) Dissolve sulfur powder in oleylamine to obtain sulfur solution;
[0013] (2) Mix cuprous iodide, zinc acetate, indium acetate, dodecyl mercaptan and oleylamine, degas and heat to obtain a copper indium zinc solution;
[0014] (3) Heat the copper-indium-zinc solution obtained in step (2) at 200-250℃ for 8-12 min, add the sulfur solution obtained in step (1) dropwise, heat at 180-220℃ for 18-22 min, quench in cold water, and obtain the reaction mother liquor.
[0015] (4) Mix mercaptopropionic acid and dimethylformamide, add the reaction mother liquor prepared in step (3), degas, heat, quench in cold water, then precipitate with n-propanol, dissolve the precipitate in deionized water to obtain Defect-CuInS2 solution, i.e. water-soluble quantum dot solution rich in edge defects.
[0016] Furthermore, in step (1), the molar volume ratio of sulfur powder and oleylamine is 1-3 mmol: 3-5 mL.
[0017] Furthermore, in step (1), the molar volume ratio of sulfur powder to oleylamine is 2 mmol: 4 mL.
[0018] Furthermore, in step (2), the molar volume ratio of cuprous iodide, zinc acetate, indium acetate, dodecyl mercaptan and oleylamine is 0.1-0.15 mmol: 0.4-0.6 mmol: 0.8-1.2 mmol: 3-6 mL: 3-6 mL.
[0019] Furthermore, in step (2), the molar volume ratio of cuprous iodide, zinc acetate, indium acetate, dodecyl mercaptan and oleylamine is 0.125 mmol: 0.5 mmol: 1 mmol: 5 mL: 5 mL.
[0020] Furthermore, in step (2), the gas is degassed for 25-35 minutes under vacuum conditions and at 80-100℃.
[0021] Furthermore, in step (2), the mixture is heated for 10-20 minutes under a nitrogen atmosphere and at 130-150°C.
[0022] Furthermore, in step (3), the volume ratio of the copper-indium-zinc solution to the sulfur solution is 8-12:4.
[0023] Furthermore, in step (4), the volume ratio of mercaptopropionic acid, dimethylformamide, the reaction mother liquor obtained in step (3), and n-propanol is 3-5:20-26:2:25-35.
[0024] Furthermore, in step (4), the volume ratio of mercaptopropionic acid, dimethylformamide, the reaction mother liquor obtained in step (3), and n-propanol is 4:24:2:30.
[0025] Furthermore, in step (4), the gas is degassed for 25-35 minutes under vacuum conditions at 45-55℃.
[0026] Furthermore, in step (4), the mixture is heated for 10-20 minutes under a nitrogen atmosphere and at 100-130°C.
[0027] Furthermore, in step (4), the concentration of the water-soluble quantum dot solution rich in edge defects is 0.06-0.07 g / L.
[0028] The present invention also provides a method for constructing the above system, comprising the following steps: adding a water-soluble quantum dot solution rich in edge defects, deionized water and polyethylene terephthalate fragments into a stoppered glass bottle, stirring evenly, and placing it under light conditions to obtain a quantum dot-based light-driven PET plastic degradation coupled with water reduction hydrogen production system.
[0029] Next, add a stir bar and stir for 2-5 minutes.
[0030] Next, stir well, remove the stir bar, tighten the stopper, and place it under light.
[0031] The present invention also provides the application of the above system in photo-driven water reduction for hydrogen production.
[0032] The present invention has the following beneficial effects:
[0033] 1. The system of this invention provides a pathway that satisfies both solar energy conversion and assists in plastic degradation. A hydrogen production system for PET plastic degradation-assisted hydrogen generation has been developed. By coupling the degradation reaction of waste PET plastic with a water reduction hydrogen production reaction, a hole sacrificial agent (PET plastic) with economical oxidative degradation effects is used to replace the common ascorbic acid sacrificial agent with no added value in degradation. This substitution improves the economic efficiency of the system, and can degrade and recycle plastics while generating hydrogen.
[0034] 2. This invention utilizes a dual-solvent method to fully exchange nonpolar ligands on the surface of quantum dots, transforming them into polar ligands. This optimizes the quantum dot preparation process. This invention provides a quantum dot rich in edge defects as a photoactive catalyst. The introduction of edge defects also provides highly active edge reaction sites. At the same time, a large number of in-band electronic intermediate states are generated in the energy band of the catalyst. The introduction of these in-band electronic intermediate states lowers the reaction energy barrier of the hydrogen generation reaction and provides more charge carrier channels, avoiding photocorrosion of the catalyst and solving the key problem of low activity of existing photocatalysts without noble metal support.
[0035] 3. The quantum dot catalyst of this invention can maintain a stable dispersion in the form of a colloidal aqueous solution, thus eliminating the need for stirring and saving energy. The light-driven PET plastic degradation coupled with water reduction to produce hydrogen of this invention does not require stirring in actual working conditions. Under natural light irradiation for up to 3 days, the quantum dots did not settle. More importantly, under sunlight irradiation, this system can reduce water to produce hydrogen while simultaneously degrading polyethylene terephthalate plastic, achieving a hydrogen generation rate of 2.1 mmol / g / hour. Attached Figure Description
[0036] Figure 1 This is a photo of the system before it was illuminated and stirred.
[0037] Figure 2 This is a photo of the system in operation. Detailed Implementation
[0038] The principles and features of the present invention are described below with reference to the accompanying drawings. The examples given are for illustrative purposes only and are not intended to limit the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer should be followed. Reagents or instruments whose manufacturers are not specified are all commercially available products.
[0039] Example 1:
[0040] A quantum dot-based light-driven PET plastic degradation coupled with water reduction hydrogen production system is constructed by the following steps:
[0041] (1) Dissolve 2 mmol of sulfur powder in 4 mL of oleylamine to prepare a sulfur solution;
[0042] (2) Mix 0.125 mmol cuprous iodide, 0.5 mmol zinc acetate, 1 mmol indium acetate, 5 mL dodecyl mercaptan and 5 mL oleylamine, place them in a 50 mL three-necked flask, degas under vacuum at 90 °C for 30 min, and heat under nitrogen atmosphere at 140 °C for 15 min to obtain copper indium zinc solution.
[0043] (3) Heat the copper indium zinc solution obtained in step (2) at 230°C for 10 min to nucleate quantum dots. Add the sulfur solution obtained in step (1) dropwise with a syringe and heat at 200°C for 20 min to grow quantum dots. Then place the three-necked flask of the reaction apparatus in cold water to quench it and obtain the reaction mother liquor (transfer to a centrifuge tube for collection and store in a 4°C refrigerator).
[0044] (4) Mix 4 mL of mercaptopropionic acid and 24 mL of dimethylformamide and place them in a 50 mL three-necked flask. Add 2 mL of the reaction mother liquor prepared in step (3). Degas under vacuum at 50 °C for 30 min, and heat under nitrogen atmosphere at 120 °C for 15 min to allow the ligands on the surface of the quantum dots to be fully exchanged. Then quench the reaction apparatus in cold water and precipitate it with 30 mL of n-propanol. Dissolve the precipitate in 30 mL of deionized water to obtain Defect-CuInS2 solution, which is a water-soluble quantum dot solution rich in edge defects (concentration of 0.067 g / L, transferred to a centrifuge tube for collection and stored in a 4 °C refrigerator).
[0045] (5) Add 3 mL of the water-soluble quantum dot solution rich in edge defects obtained in step (4), 2 mL of deionized water, and 100 mg of polyethylene terephthalate fragments (0.5 cm in diameter) to a 50 mL glass bottle with a stopper. Stir for 3 min, and after thorough mixing, remove the stir bar, seal the bottle, and place it under outdoor sunlight to obtain a quantum dot-based light-driven PET plastic degradation coupled with water reduction hydrogen production system (see...). Figure 1 ).
[0046] Example 2:
[0047] A quantum dot-based light-driven PET plastic degradation coupled with water reduction hydrogen production system is constructed by the following steps:
[0048] (1) Dissolve 1 mmol of sulfur powder in 3 mL of oleylamine to prepare a sulfur solution;
[0049] (2) Mix 0.1 mmol cuprous iodide, 0.4 mmol zinc acetate, 0.8 mmol indium acetate, 3 mL dodecanethiol and 3 mL oleylamine, place them in a 50 mL three-necked flask, degas under vacuum at 80 °C for 25 min, and heat under nitrogen atmosphere at 130 °C for 10 min to obtain copper indium zinc solution.
[0050] (3) The copper-indium-zinc solution obtained in step (2) was heated at 200°C for 8 min to nucleate quantum dots. The sulfur solution obtained in step (1) was added dropwise with a syringe, and the solution was heated at 180°C for 18 min to grow quantum dots. Then, the three-necked flask of the reaction apparatus was placed in cold water to quench the reaction and obtain a solution containing WU-V. Cu -The reaction mother liquor of CuInS2, i.e., the water-insoluble reaction mother liquor rich in edge defect quantum dots (transfer to centrifuge tubes for collection and store in a 4°C refrigerator);
[0051] (4) Mix 3 mL of mercaptopropionic acid and 20 mL of dimethylformamide and place them in a 50 mL three-necked flask. Add 2 mL of the reaction mother liquor prepared in step (3). Degas under vacuum at 45 °C for 25 min. Heat under nitrogen atmosphere at 100 °C for 10 min to allow the ligands on the surface of the quantum dots to be fully exchanged. Then quench the reaction apparatus in cold water and precipitate it with 25 mL of n-propanol. Dissolve the precipitate in deionized water to obtain Defect-CuInS2 solution, which is a water-soluble quantum dot solution rich in edge defects (concentration of 0.06 g / L, transferred to a centrifuge tube for collection and stored in a 4 °C refrigerator).
[0052] (5) Add 3 mL of water-soluble quantum dot solution rich in edge defects, 1 mL of deionized water and 80 mg of polyethylene terephthalate fragments (0.4 cm in diameter) obtained in step (4) to a 50 mL glass bottle with a stopper. Stir for 2 min, shake well, remove the stir bar, stopper the bottle, and place it under outdoor sunlight to obtain a quantum dot-based light-driven PET plastic degradation coupled water reduction hydrogen production system.
[0053] Example 3:
[0054] A quantum dot-based light-driven PET plastic degradation coupled with water reduction hydrogen production system is constructed by the following steps:
[0055] (1) Dissolve 3 mmol of sulfur powder in 5 mL of oleylamine to prepare a sulfur solution;
[0056] (2) Mix 0.15 mmol cuprous iodide, 0.6 mmol zinc acetate, 1.2 mmol indium acetate, 6 mL dodecanethiol and 6 mL oleylamine, place them in a 50 mL three-necked flask, degas under vacuum at 100 °C for 35 min, and heat under nitrogen atmosphere at 150 °C for 20 min to obtain copper indium zinc solution.
[0057] (3) The copper-indium-zinc solution obtained in step (2) was heated at 250°C for 12 min to nucleate quantum dots. The sulfur solution obtained in step (1) was added dropwise with a syringe, and the solution was heated at 220°C for 22 min to grow quantum dots. Then, the three-necked flask of the reaction apparatus was placed in cold water to quench the reaction and obtain a product containing WU-V. Cu -The reaction mother liquor of CuInS2, i.e., the water-insoluble reaction mother liquor rich in edge defect quantum dots (transfer to centrifuge tubes for collection and store in a 4°C refrigerator);
[0058] (4) Mix 5 mL of mercaptopropionic acid and 26 mL of dimethylformamide and place them in a 50 mL three-necked flask. Add 2 mL of the reaction mother liquor prepared in step (3). Degas under vacuum at 55 °C for 35 min, and heat under nitrogen atmosphere at 130 °C for 20 min to allow the ligands on the surface of the quantum dots to be fully exchanged. Then place the three-necked flask of the reaction apparatus in cold water to quench it. Then use 35 mL of n-propanol to precipitate it. Dissolve the precipitate with deionized water to obtain Defect-CuInS2 solution, i.e., water-soluble quantum dot solution rich in edge defects (concentration of 0.07 g / L, transferred to centrifuge tube for collection and stored in a 4 °C refrigerator).
[0059] (5) Add 3 mL of water-soluble quantum dot solution rich in edge defects, 3 mL of deionized water and 90 mg of polyethylene terephthalate fragments (0.6 cm in diameter) obtained in step (4) to a 50 mL glass bottle with a stopper. Stir for 5 min, shake well, remove the stir bar, stopper the bottle, and place it under outdoor sunlight to obtain a quantum dot-based light-driven PET plastic degradation coupled water reduction hydrogen production system.
[0060] Comparative Example 1:
[0061] A quantum dot-based light-driven PET plastic degradation coupled with water reduction hydrogen production system is constructed by the following steps:
[0062] In step (2), 1 mmol of cuprous iodide is used.
[0063] In step (4), a CuInS2 solution, i.e. a water-soluble quantum dot solution, is prepared;
[0064] The rest is the same as in Example 1.
[0065] Comparative Example 2:
[0066] A hydrogen production system based on titanium dioxide-driven photocatalytic degradation of PET plastic coupled with water reduction is constructed by the following steps:
[0067] In step (5), the water-soluble quantum dots rich in edge defects are replaced with commercially available titanium dioxide P25 white powder, and the rest is the same as in Example 1.
[0068] Comparative Example 3:
[0069] A quantum dot-based light-driven water reduction hydrogen production system is constructed using the following steps:
[0070] In step (5), the polyethylene terephthalate fragments are replaced with ascorbic acid, and the rest is the same as in Example 1.
[0071] Test case
[0072] The following hydrogen generation rates ( / mmol / h / g) refer to the number of millimoles of hydrogen generated per gram of quantum dots per hour.
[0073] 1. The hydrogen production systems obtained in Example 1 and Comparative Examples 1-3 were subjected to performance testing, with outdoor natural sunlight as the light source (see...). Figure 2 The results are shown in Table 1.
[0074] Table 1. Test data for hydrogen production via water reduction.
[0075]
[0076] As shown in Table 1, the water-soluble quantum dot Defect-CuInS2 of the present invention exhibits the best light-driven water reduction hydrogen generation rate while degrading PET plastic; and its performance is about 5 times better than that of water-soluble quantum dot CuInS2, and about 20 times better than that of commercial photocatalyst titanium dioxide P25.
[0077] As shown in Table 1, by changing the sacrificial agent and replacing PET plastic with easily oxidized ascorbic acid, the hydrogen production rate was increased by nearly three times. This indicates that plastic degradation is indeed more difficult than ascorbic acid oxidation. However, degrading plastic is more economical than the non-value-added oxidation of ascorbic acid, which makes our fuel generation system have certain practical significance.
[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A quantum dot-based light-driven PET plastic degradation coupled with water reduction hydrogen production system, characterized in that, The system includes a stoppered glass bottle containing water-soluble quantum dots rich in edge defects, deionized water, and polyethylene terephthalate fragments. The water-soluble quantum dots rich in edge defects were prepared by the following method: (1) Dissolve sulfur powder in oleylamine to obtain a sulfur solution; (2) Mix cuprous iodide, zinc acetate, indium acetate, dodecyl mercaptan and oleylamine, degas and heat to obtain a copper indium zinc solution; (3) Heat the copper-indium-zinc solution obtained in step (2) at 200-250℃ for 8-12 min, add the sulfur solution obtained in step (1) dropwise, heat at 180-220℃ for 18-22 min, quench in cold water, and obtain the reaction mother liquor. (4) Mix mercaptopropionic acid and dimethylformamide, add the reaction mother liquor prepared in step (3), degas, heat, quench in cold water, then use n-propanol to precipitate, dissolve the precipitate in deionized water to obtain Defect-CuInS2 solution, i.e. water-soluble quantum dot solution rich in edge defects. In step (2), the molar volume ratio of cuprous iodide, zinc acetate, indium acetate, dodecyl mercaptan and oleylamine is 0.1-0.15 mmol: 0.4-0.6 mmol: 0.8-1.2 mmol: 3-6 mL: 3-6 mL.
2. The quantum dot-based light-driven PET plastic degradation coupled with water reduction hydrogen production system according to claim 1, characterized in that, When the volume of the stoppered glass bottle is 45-55 mL, the mass-to-volume ratio of the water-soluble quantum dots rich in edge defect, deionized water, and polyethylene terephthalate fragments is 0.18-0.21 mg: 4-6 mL: 90-110 mg.
3. The quantum dot-based light-driven PET plastic degradation coupled with water reduction hydrogen production system according to claim 2, characterized in that, When the stoppered glass bottle has a volume of 50 mL, the mass-to-volume ratio of the water-soluble quantum dots rich in edge defect, deionized water, and polyethylene terephthalate fragments contained therein is 0.2 mg: 5 mL: 100 mg.
4. The quantum dot-based light-driven PET plastic degradation coupled with water reduction hydrogen production system according to any one of claims 1-3, characterized in that, The diameter of polyethylene terephthalate fragments is 0.4-0.6 cm.
5. The quantum dot-based light-driven PET plastic degradation coupled with water reduction hydrogen production system according to claim 1, characterized in that, In step (1), the molar volume ratio of sulfur powder and oleylamine is 1-3 mmol: 3-5 mL.
6. The method for constructing a quantum dot-based light-driven PET plastic degradation coupled with water reduction hydrogen production system according to any one of claims 1-5, characterized in that, Includes the following steps: A water-soluble quantum dot solution rich in edge defects, deionized water, and polyethylene terephthalate fragments were added to a stoppered glass bottle, stirred evenly, and placed under light conditions to obtain a quantum dot-based light-driven PET plastic degradation coupled with water reduction hydrogen production system.
7. The method for constructing a quantum dot-based light-driven PET plastic degradation coupled with water reduction hydrogen production system according to claim 6, characterized in that, Add a mixer and stir for 2-5 minutes.
8. The application of the quantum dot-based light-driven PET plastic degradation coupled with water reduction hydrogen production system according to any one of claims 1-5 in light-driven water reduction hydrogen production.
Citation Information
Patent Citations
Method of preparing quaternary sulfide quantum dot photocatalyst
CN107297213A
Quantum dot sensitized oxide electrode and preparation method and application thereof
CN115410829A
